Essential Oil Compounds of Three Nepeta L. Taxa From Turkey and Their Chemotaxonomy - Kilic, Omer; Behcet, Lutfi; Bagci, Eyup (Asian Journal of Chemistry, 2013)
The essential oil aerial parts of Nepeta baytopii Hedge and Lamond., Nepeta cataria L. and Nepeta fissa C. A. Mey. were investigated by GC and GC-MS. The yield of oils are ca. 0.40, 0.45 and 0.50 mL/100 g, respectively. Forty six, fourty seven and forty nine compounds were identified representing 92.4, 91.2 and 92.5 % of the oil, respectively. 1,8-Cineole (23.2 %) and nepetalactone (12.8 %) in N. baytopii, nepetalactone (27.5 %) - 1,8-cineole (10.8 %) and germacrene D (9.2 %) in N. cataria, 1,8-cineole (24.3 %) and nepetalactone (17.6 %) were identified as major components in N. fissa. The chemical distribution of the essential oil compounds in the genus pattern were discussed in means of chemotaxonomy.
Keywords: Nepeta; Lamiaceae; Essential oil; Chemotaxonomy